Hubungan Self-Efficacy dan Self-Regulated Learning Terhadap Hasil Belajar Siswa SD Kelas V di Gugus Dwija Krida Kota Semarang - Arina Futri Murohkhamah; Sri Sami Asih (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the relationship between self-efficacy and self-regulated learning (SRL) on the learning outcomes of fifth-grade elementary school students in the Dwija Krida Cluster, Semarang City. This research employed a quantitative approach with a correlational design. The sample consisted of 116 fifth-grade students selected through purposive sampling. Data were collected using a 4-point Likert scale questionnaire to measure self-efficacy and SRL, while learning outcomes were obtained from the students' even semester report cards. The results of the analysis indicated a positive and significant relationship between self-efficacy and learning outcomes, as well as between SRL and learning outcomes. Simultaneously, self-efficacy and SRL contributed 52% to the variance in learning outcomes. These findings highlight the importance of strengthening self-efficacy and developing SRL to enhance students' academic achievement.